Mathematics In Context: Call of Time - Quaiyum, Abdul (Academic Voices: A Multidisciplinary Journal, 2011)
Mathematics in context (MiC) is an integrated program that uses Realistic Mathematics Education(RME) approach to teaching and learning of mathematics. It emphasizes learning mathematics from realistic situations, students’ invention or construction of solution procedure and interaction with other students or the teacher. Students should be encouraged to make sense out of real problems and the mathematics instruction should be designed accordingly. This article deals with the underlying principles of RME and highlights the features of MiC in Nepalese Mathematics Education. Keywords Realistic Mathematics Education (RME), Mathematics in Context (MiC), didactical phenomenology, guided reinvention, emergent model DOI: http://dx.doi.org/10.3126/av.v1i0.5299 Academic Voices 2011; 1: 1-5